2021
DOI: 10.1371/journal.pone.0239502
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of water source use, quality of water, sanitation and hygiene perceptions among urban households in North-West Ethiopia: A cross-sectional study

Abstract: Background Clean water is an essential part of human healthy life and wellbeing. More recently, rapid population growth, high illiteracy rate, lack of sustainable development, and climate change; faces a global challenge in developing countries. The discontinuity of drinking water supply forces households either to use unsafe water storage materials or to use water from unsafe sources. The present study aimed to identify the determinants of water source types, use, quality of water, and sanitation perception o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 25 publications
1
11
1
Order By: Relevance
“…Marriage increases the family size and larger families require more water and could have made a better effort to own tap water. Similarly, Gebremichael et al [ 30 ] reported a significant association of households' drinking water sources with age, educational status, and family size in northwest Ethiopia. Earlier, Fortune and Sikod [ 31 ] indicated a significant association of distance of water sources and household size with the choice of drinking water source in Cameroon.…”
Section: Discussionmentioning
confidence: 98%
“…Marriage increases the family size and larger families require more water and could have made a better effort to own tap water. Similarly, Gebremichael et al [ 30 ] reported a significant association of households' drinking water sources with age, educational status, and family size in northwest Ethiopia. Earlier, Fortune and Sikod [ 31 ] indicated a significant association of distance of water sources and household size with the choice of drinking water source in Cameroon.…”
Section: Discussionmentioning
confidence: 98%
“…The provision of latrines is one aspect of sanitation disruptions, which work to protect public health by safely containing feces and preventing their release into private and public areas (Ali, 2010). This nding is in promise with researches conducted in Debre Tabor northwest Ethiopia (Gebremichael et al, 2021)…”
Section: Bacteriological Quality Of Drinking Watermentioning
confidence: 90%
“…Access to the sources of safe drinking water and its composition vary among different populations. Nowadays, about one billion people continue to suffer from poor access to clean water [ 49 ]. However, water drinking should be recognized as one of the most important modifiable lifestyle factors, which may be a valuable confounder in CV and especially metabolic health studies of the third millennium [ 50 ].…”
Section: Discussionmentioning
confidence: 99%